2018
DOI: 10.1093/hmg/ddy225
|View full text |Cite
|
Sign up to set email alerts
|

GFPT1 deficiency in muscle leads to myasthenia and myopathy in mice

Abstract: Glutamine-fructose-6-phosphate transaminase 1 (GFPT1) is the rate-limiting enzyme in the hexosamine biosynthetic pathway which yields precursors required for protein and lipid glycosylation. Mutations in GFPT1 and other genes downstream of this pathway cause congenital myasthenic syndrome (CMS) characterized by fatigable muscle weakness owing to impaired neurotransmission. The precise pathomechanisms at the neuromuscular junction (NMJ) owing to a deficiency in GFPT1 is yet to be discovered. One of the challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 50 publications
(69 reference statements)
0
13
0
Order By: Relevance
“…All five genes code for proteins of the glycosylation pathway and procure posttranslational modifications to a wide variety of proteins including STIM1 and ORAI1. Hypoglycosylation of STIM1 and ORAI1 stimulates SOCE and extracellular Ca 2+ influx ( Selcen et al, 2014 ), and the muscle-specific deletion of Gfpt1 in mice causes myasthenia and the occurrence of tubular aggregates in muscle fibers ( Issop et al, 2018 ). These examples show that the dysfunction of proteins directly or indirectly associated with STIM1 and ORAI1 can cause human pathologies overlapping with TAM/STRMK at the clinical and histological level.…”
Section: Soce Regulators Associated Diseases and Animal Modelsmentioning
confidence: 99%
“…All five genes code for proteins of the glycosylation pathway and procure posttranslational modifications to a wide variety of proteins including STIM1 and ORAI1. Hypoglycosylation of STIM1 and ORAI1 stimulates SOCE and extracellular Ca 2+ influx ( Selcen et al, 2014 ), and the muscle-specific deletion of Gfpt1 in mice causes myasthenia and the occurrence of tubular aggregates in muscle fibers ( Issop et al, 2018 ). These examples show that the dysfunction of proteins directly or indirectly associated with STIM1 and ORAI1 can cause human pathologies overlapping with TAM/STRMK at the clinical and histological level.…”
Section: Soce Regulators Associated Diseases and Animal Modelsmentioning
confidence: 99%
“…Mutations in GFPT1 cause CMS characterized by fatigable muscle weakness owing to impaired neurotransmission. The precise pathomechanisms at the NMJ due to GFPT1 deficiency have yet to be discovered 37 . In our study, the two missense mutations in the GFPT1 mutant patient were previously reported 22–24 .…”
Section: Discussionmentioning
confidence: 71%
“…This effect resulted in recovery of muscle force and size leading to increased overall body weight, and extended life span (33). Moreover, glypican-1 has recently been linked to the pathophysiology of a muscular dystrophy complicated by a myasthenic syndrome (34) as well as of laminin α4, which has an important role in NMJ-integrity (29). However, the conclusion of endogenous activation of compensatory mechanisms in muscle of MDC1A-patients is further supported by the increase of C4b-binding protein alpha chain belonging to the complement system that deposits its activation products on innervated motor end-plates in ALS-patients (35).…”
Section: Discussionmentioning
confidence: 99%